Construction of a circular section for weighing lysimeter for the measurement of reference evapotranspiration (Et0): Three load cell system - Gomes Junior, Daniel Gonçalves [UNESP]; Dal Pai, Alexandre [UNESP]; Dal Pai, Enzo [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2019)
Evapotranspiration measurement of a given locality is very relevant for the rational use of water in agricultural systems. With this measure, it is possible to quantify with greater precision the water requirement of crops. The main objective of this work was to develop a weighing lysimeter to measure reference evapotranspiration. This equipment is composed of a concrete structure in circular format, having a visiting well with a tank with volumetric capacity of 1.50 m³. The weighing system was designed on the basis of a reinforced support tripod with carbon steel frame and three load cells affixed. Load cell measurements were stored using a Campbell Scientific® 21-X datalogger. The soil moisture maintenance, when in the field capacity, was done according to the readings obtained from the datalogger in conjunction with tensiometers / vacuometers installed to a depth of 0.20 m inside and outside of the tank, and a three-day interval of irrigation was defined. The methodology presented in this work and used in the construction, automation and calibration processes was adequate, providing a coefficient of determination (R²) of 0.9998 proving that the equipment can provide accurate measurements. As a practical result for the study environment, the average evapotranspiration value of 3.5 mm/day is a good indicative of the equipment functionality.
Construção de lisímetro de pesagem de seção circular para a medição da evapotranspiração de referência (Et0): sistema com três células de carga
Keywords: Irrigation; water flux; Water requirement